Doctrine of frustration and force majeure clause: its application on tenancy contract during the movement control order in Malaysia - Muhammad Asyraf Azni; Suria Fadhillah Md Pauzi; Ida Rosnita Ismail (Penerbit Universiti Kebangsaan Malaysia, 2021)
The government of Malaysia has declared the Movement Control Order (MCO) for the whole nation in order to flatten the curve of COVID-19 infection. The MCO has, among others, caused parties in a contract to question the effect of the MCO on the contract. As the areas of law are wide, this paper aims to discuss the effect of MCO on a tenancy contract. The paper analysed the legal position of doctrine of frustration and force majeure clause in the context of tenancy contract in Malaysia. The analysis was done based on the law cases and legal provisions in Malaysia. Reference was also made to case law from the United Kingdom and Singapore as their law is in pari materia with Malaysian law and they are persuasive in nature. This paper found that the doctrine of frustration can be invoked if the performance of the obligation under the tenancy contract is prevented due to the MCO. However, the court will apply the doctrine of frustration in a very careful manner to respect the sanctity of the agreement. As for the force majeure clause, it can be successfully invoked if the scope of the clause covers the event in question, such as the MCO. In conclusion, whether a tenancy contract can be terminated due to the MCO, it will depend on the terms of each tenancy contract.